Effects of iron doping on catalytic oxidation activity of Mn-based co-oxide filter media for removal of ammonium and manganese from groundwater. (15th January 2022) - Cheng, Ya; Zhang, Yongzhi; Xiong, Weiyao; Huang, Tinglin; Tang, Huan
Abstract: Mn-based co-oxides filter media with different Fe/Mn molar ratios were synthesized to investigate the influence of Fe doping on the catalytic activities for ammonium and manganese removal. A pilot-scale filter column system was adopted to prepare the filter media and the actual Fe amount in filter media was regulated during the start-up period. Mn-based co-oxides with a Fe/Mn molar ratio of 1:2 presented excellent catalytic property, and the removal efficiency of the ammonium and manganese of the filter reached over 90% on the 7th and 15th days, respectively. A large Fe doping ratio (Fe/Mn = 2:2) was not conducive to the improvement of the catalytic activity. An extended characterization of the Mn-based co-oxides samples with different Fe/Mn molar ratios by X-ray diffraction (XRD), Fourier transform-infrared spectroscopy (FTIR), and X-ray photoelectron spectroscopy (XPS) was performed. The modification of Fe in the Mn-based co-oxides filter media was found to inhibit the formation of crystal clusters, increase the proportion of Mn 3+ content on the surface, and promote the formation of defects of the lattice oxygen. These modifications led to the enhancement of the electron transfer capacity in the catalytic reaction. In addition, the doped Fe mainly existed in the form of FeOOH and Fe2 O3 . With increased Fe doping, the amount of FeOOH increased and Fe2 O3 decreased. Fe2 O3 facilitated interfacial charge transfer, which may be the reason for the high catalytic activity. These results indicate that Fe doping is an effective method for accelerating catalytic activity formation during the start-up period of Mn-based co-oxides filters for ammonium and manganese removal. This study provides new insights on the interaction mechanisms between Fe and Mn-based co-oxides and on the catalytic oxidation of ammonium and manganese. Highlights: Mn-based co-oxides with Fe/Mn molar ratio of 1:2 exhibited excellent catalytic performance. Highest catalytic activity for NH4 + -N and Mn 2+ ions oxidation in Mn-based co-oxides. The modification of Fe led to the enhancement of the electron transfer capacity. Insights for the regulation of the catalytic activity of Mn-based co-oxides.